2018
DOI: 10.1002/biof.1461
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐96 protects pancreatic β‐cell function by targeting PAK1 in gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is a disease condition in which a woman develops high blood sugar levels during pregnancy, which might be induced by multiple factors. Among those relative factors, microRNA (miRNA) is well-known to be involved in GDM development. In this study, we investigated the role of miRNA in GDM by analyzing miRNA expression profiling in placenta tissues from healthy or GDM pregnancies. We found that miR-96 was the most down-regulated miRNA in GDM samples. Furthermore, miRNA target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Similarly, Li et al evaluated microRNA expression in placental tissue from three GDM and three CTRLs [90]. A significant downregulation of miR-96 was reported in GDM compared to CTRLs and an inverse correlation between miR-96 expression and blood glucose emerged.…”
Section: β-Cell Dysfunctionmentioning
confidence: 99%
“…Similarly, Li et al evaluated microRNA expression in placental tissue from three GDM and three CTRLs [90]. A significant downregulation of miR-96 was reported in GDM compared to CTRLs and an inverse correlation between miR-96 expression and blood glucose emerged.…”
Section: β-Cell Dysfunctionmentioning
confidence: 99%
“…Accumulating studies have suggested miRNAs are closely related to glycometabolic disorders including GDM by regulating placental immunity, pancreatic β cell functions, insulin sensitivity, and insulin resistance [14][15][16]. Circulating miRNAs contributing to tissue cross-talk have also been identified as potential biomarkers for GDM [17].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…The regulation of miRNAs on target genes is also a hot spot in oncology. Studies have revealed that miR-485-5p 79 , miR-140-5p 80 , miR-96 81 , miR-7 82 , miR-494 83 , miR-34b 84 , and miR-145 85 can directly target and degrade the mRNA of PAK1 in order to block the translation of PAK1. In addition, PAK1 can be directly activated by interaction with Rho-related GTPases CDC42 and RAC1 86 .…”
Section: Endogenous Upstream Regulators Of Pak1mentioning
confidence: 99%